(untitled) (Biological Sciences - PJSIR, 1998)
In laboratory experiments, Baythroid (an insecticide produced by Bayer, West Germany) was compared with N- Serve (a well-known nitrification inhibitor) for its effect 011 the process of nitrification in oil. In one experiment, soil samples were incubated for 7 week at 30°C after treatment with Baythroid (0.4, 1.6, or 6.4 ug g.1 soil) or with N-Serve (1.1,4.4. and 17.61-lg g’ soil); 200 ug s:’ soil N as ammonium sulphate was applied in all cases. Soil samples analyzed at different incubation intervals revealed significant inhibition of nitrification and accumulation of NHJ-N due to both the chemicals and the effects increased with the rate of application. At lower levels of inhibitors, the effect was short-lived, while at higher levels limited amounts or N03-N were observed after 7 weeks of incubation. N-Serve was found to be more inhibitory to nitrification as compared with Baythroid. In another experiment where soil samples treated with Baythroid (at 0.4, 0.8, 1.6, 3.2, or 6.4 lAg g.J soil) and N-Serve (1.1, 2.2, 4.4, 8.8, or 17.6 ug s:’ soil) were incubated for 10, 20 and 30 days prior to addition of N (200 ug g.1 soil as ammonium sulphate), N-Serve was found to be more persistent in inhibiting nitrification as compared with Baythroid. It is proposed that some microbial processes, nitrification in the present case, could be used as an indicator of persistence of some xenobiotics,